Commentary of confirmation to the judgement of the Voivodship Administrative Court in Łódź of 30 November 2021, Ref. No. I SA/Łd 699/21 - Ciupa, Gracjan (Wydawnictwo C.H. Beck, 2023)
The subject of this commentary is the judgement of the Voivodship Administrative Court (WSA) in Łódź of 30 November 2021, ref. I SA/Łd 699/21. This judgement concerns the interpretation of the Director of the National Fiscal Information of 27 July 2021. The tax authority interpreted Article 22(14) of the Personal Income Tax Act of 26 July 1991, in accord-ance with which it held that the purchase of electrical energy necessary for the operation of cryptocurrency mining hardware and the purchase of computer equipment for the construction of cryptocurrency mining hardware should not qualify as tax-deductible costs for the paid disposal of virtual currency. The author of the commentary takes a position in line with the judgement of the WSA, which recognizes these expenses as tax-deductible costs. The commentary presents, among other things, the author’s views on the “directness” of the costs and regulations of cryptocurrencies.